Serum Albumin Level in Third Trimester of Pregnancy and Non-Pregnant Women: A Comparative Study (Journal of Monno Medical College, 2026)
Background: Serum albumin level is an predictor for preeclamplsia and eclampsia.Objective: The purpose of the present study was to compare the levels of serum albumin in third trimester of pregnancy with non-pregnant women of same age range.Methodology: This analytical type of cross-sectional study was carried out in the Department of Physiology, Mymensingh Medical College, Mymensingh, Bangladesh over one year. A total number of 140 subjects, age range between 20 to 35 years were included in this study. Among them, 70 healthy subjects were taken as control group (Group I) and 70 pregnant women of third trimester were taken as study group (Group II). The results were calculated and analyzed by using SPSS. Quantitative data were expressed as mean (±SE) and statistical significance of difference among the group was calculated by unpaired student’s ʻtʼ test.Results: In this study we found that Serum albumin level of group I (Control group) was 4.03±0.36 gm/dl and group II (Study group) was 3.03±0.48 gm/dl. In group II Serum Albumin level was decreased in comparison to group I. The difference of mean Serum Albumin level between the groups was statistically highly significant (p